Factors Associated with Interpersonal Violence and Depression Symptoms in Adolescent Students from Jalisco during the COVID-19 Pandemic - Andrade, Evangelina Díaz; Bolaños, Rosibel Rodríguez; Carmona, Anabel Rojas; Palacios, Paula Ramírez; Santillán, Edna Arillo; Gutiérrez, Inti Barrientos; Pérez, Dèsirée Vidaña; Thrasher, James F (Salud mental (México), 2024)
Violence is a major public health problem, which increased during the Covid-19 pandemic, affecting the physical and mental development of adolescents. To analyze factors associated with interpersonal violence and depressive symptoms in adolescent students in the South of Jalisco. Data were drawn from an online survey of 3,046 adolescents (12-19 years) conducted between September and December 2021. The Beck Depression Inventory was used to assess depressive symptoms. Self-report of neglect, physical, psychological, sexual, and digital violence in the previous 12 months were analyzed. Bivariate and multivariate logistic regression models explored factors associated with depression and violence. A total of 28.8% of the sample reported depressive symptoms, 46.9% physical violence, 42.7% psychological violence, 34.9% neglect, 12.3% digital violence, and 5.2% sexual violence. The odds of depression were higher for those who experienced physical violence (adjusted odds ratio [aOR]=1.3 CI95% [1.1-1.6]), psychological and (aOR=4.1 CI95% [3.4-5.1]), digital violence (aOR=2.0 CI95% [1.5-2.5]); and neglect (aOR=1.6 CI95% [1.3-1.9]). Grils and adolescents aged 15-19 years, had higher odds of experiencing sexual, digital, and psychological violence. Poor school performance was associated with lower odds of reporting neglect (aOR=0.6 CI95% [0.5-0.8]) and sexual violence (aOR=0.5 CI95% [0.3-0.8]), while being employed was associated with reporting higher odds of physical violence (aOR=1.5 CI95% [1.3-1.8]) and neglect (aOR=1.3 CI95% [1.1-1.5]). Greater use of social networks and videogames was associated with higher odds of physical, psychological, and digital violence. It is necessary to implement comprehensive public programs and policies to address violence and implement intersectoral social intervention strategies in mental health.